The Finance-Growth Nexus: An Empirical Analysis from Brazil - Marques, Francisco; Almeida, Patricia; Silva, Marcia (Journal of Accounting, Business and Finance Research, 2020)
A well-established financial system is very crucial for the economic growth and development of any country. There are many aspects that are studied in relation with financial development such as savings, investments, and technical innovations etc. which affect the growth of economy in a country in one way or the other. In this context, the researcher has designed this study to explore the relationship amid financial development and economic growth of Brazil, which is clear from the title of the study i.e. finance-growth nexus. In continuation of this objective, the researcher has collected data from Brazil and the collected data is time series. The period for which the data has been gathered comprises of 30 years and has been collected from the most authentic sources of data or databases such as World Bank Development. The collected data has been analyzed by applying the techniques such as unit root, bounds test and ARDL estimation. These results indicate that private credit has noteworthy along with positive impact on economic growth. The next result of the study suggests that gross domestic saving does not pose any momentous impact on the economic growth of the country. The impact of trade openness has been found as significant along with negative in Brazil. The inflation has significant but negative impact on economic growth in longer run but this impact is insignificant in shorter run.